2013
DOI: 10.1007/s11434-013-5806-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and cloning of a brittle culm mutant (bc88) in rice (Oryza sativa L.)

Abstract: This study characterizes a brittle culm (bc88) mutant of rice (Oryza sativa L.) obtained by ethylene methylsulfonate (EMS)-induced mutagenesis of Wuyunjing 7. The bc88 mutant exhibits a diversity of pleiotropic phenotypes, including brittle culm at the whole-plant growth stages, withered leaf tips at the seedling stage, and 18-d delay in heading date at the mature stage. Genetic analysis indicates that the bc88 mutant is controlled by a single recessive nuclear gene. The mutated bc88 gene isolated by map-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Therefore, although the Sdbc1 and Bc6 mutants exhibited a semi-dominant brittle phenotype, the mechanism for the dominant negative effect differs. The sdbc1 and bc6 mutation occurs in the region between TMD2 and TMD3, but not all mutations that occur in this region exhibit semi-dominant phenotype, such as the osfc16 and bc88 mutant mutations located between sdbc1 and bc6 mutation sites (Figure 3c), However, these two mutants are recessive and show obviously different phenotypes (Li et al, 2017, Rao et al, 2013. The osfc16 mutant with substitutions (W481C, P482S) in OsCESA9 shows slightly affected plant growth and signi cantly reduced cellulose crystallinity (CrI) and thinner secondary cell walls (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, although the Sdbc1 and Bc6 mutants exhibited a semi-dominant brittle phenotype, the mechanism for the dominant negative effect differs. The sdbc1 and bc6 mutation occurs in the region between TMD2 and TMD3, but not all mutations that occur in this region exhibit semi-dominant phenotype, such as the osfc16 and bc88 mutant mutations located between sdbc1 and bc6 mutation sites (Figure 3c), However, these two mutants are recessive and show obviously different phenotypes (Li et al, 2017, Rao et al, 2013. The osfc16 mutant with substitutions (W481C, P482S) in OsCESA9 shows slightly affected plant growth and signi cantly reduced cellulose crystallinity (CrI) and thinner secondary cell walls (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The osfc16 mutant with substitutions (W481C, P482S) in OsCESA9 shows slightly affected plant growth and signi cantly reduced cellulose crystallinity (CrI) and thinner secondary cell walls (Li et al, 2017). The bc88 mutant, which harbors the substitution (P421L) in OsCESA9 exhibits a diversity of pleiotropic phenotypes, including a brittle culm phenotype, dwar sm, withered leaf tips at the seedling stage, and an 18-d delay in heading date at the mature stage (Rao et al, 2013). Studies of these mutants suggest that the different conserved sites in the central cytoplasmic domain play a distinct role in cellulose synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have isolated at least 11 bc mutants, including bc1, bc2, bc3, bc4, bc5, BC6, bc7, bc10, bc11, bc12, and bc15 (Li et al 2003;Yan et al 2007;Aohara et al 2009;Zhang et al 2009;Hirano et al 2010;Zhang et al 2010;Kotake et al 2011;Wu et al 2012;Rao et al 2013). Nine of these genes have been cloned and further characterization showed a division into two categories: the first category is comprised of cell wall biosynthetic genes, including OsCesA4/BC7/BC11, OsCesA7 and OsCesA9/bc6 (Tanaka et al 2003;Yan et al 2007;Zhang et al 2009;Kotake et al 2011;Wang et al 2012;Rao et al 2013), while the second category consists of regulatory factors that indirectly function in cell wall biosynthesis, including BC1, BC3, BC10, BC12, and BC15 (Li et al 2003;Hirano et al 2010;Zhang et al 2010;Wu et al 2012). Additionally, a recent report showed that the BSH1 gene, encoding an OsCYP96B4 protein, functions in the secondary cell wall formation in an unknown manner (Wang et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several genes directly involved in cell wall biosynthesis have already been identified and characterized with mutants of this type. For example, the disruptions of CesA (Cellulose synthase catalytic subunit) genes, OsCesA4/BC7/BC11, OsCesA7 and OsCesA9/bc6, cause a dramatic reduction in cellulose content and the mechanical strength of plant tissues, suggesting their essential roles in synthesis of the secondary cell wall in rice (Tanaka et al 2003;Yan et al 2007;Zhang et al 2009;Kotake et al 2011;Wang et al 2012;Rao et al 2013). Additionally, regulatory mutations, indirectly involved in cell wall synthesis, also cause fragility in plant tissues.…”
Section: Introductionmentioning
confidence: 99%
“…His research paper about male sterility of rice published in Chinese Science Bulletin [6] opens the era of ''Second Green Revolution'' and revolutionizes rice cultivation in China, establishing China's world-leading position in hybrid rice research and farming. Ever since then, studies about rice development [7][8][9], genetic analysis and disease resistance [10][11][12][13][14][15][16][17] have constantly been the focused disciplines of Science Bulletin. Together with rice, researches on other important crops, such as cotton [18][19][20][21][22][23], wheat [24-26] and the model plant Arabidopsis [27-32], have led to further understandings of plant physiology and the mechanisms of disease resistance.…”
mentioning
confidence: 99%